Inhibitory effect of novel iron chelator, 1-(N-acetyl-6-aminohexyl)-3-hydroxy-2-methylpyridin-4-one (CM1) and green tea extract on growth of Plasmodium falciparum - Thipubon, Phitsinee (Malar J, 2015)
BACKGROUND: Iron is an essential micronutrient required by all living organisms including malaria parasites (Plasmodium spp.) for many biochemical reactions, especially growth and multiplication processes. Therefore, malaria parasite needs to take up the iron from outside or/and inside the parasitized red blood cells (PRBC). Iron chelators are widely used for the treatment of thalassaemia-related iron overload and also inhibit parasite growth at levels that are non-toxic to mammalian cells. METHODS: Inhibitory effect of 1-(N-acetyl-6-aminohexyl)-3-hydroxy-2-methylpyridin-4-one (CM1) and green tea extract (GTE) on the growth of malaria parasite Plasmodium falciparum was compared with standard chelators including desferrioxamine (DFO), deferiprone (DFP) and deferasirox (DFX). A flow cytometric technique was used to enumerate PRBC stained with SYBR Green I fluorescent dye. The labile iron pool (LIP) was assayed using the calcein-acetoxymethyl fluorescent method. RESULTS: The IC(50) values of DFO, GTE, CM1, DFX and DFP against P. falciparum were 14.09, 21.11, 35.14, 44.71 and 58.25 µM, respectively. Importantly, CM1 was more effective in reducing LIP levels in the P. falciparum culture than DFP (p < 0.05). CONCLUSIONS: CM1 and GTE exhibit anti-malarial activity. They could interfere with uptake of exogenous iron or deplete the intracellular labile iron pool in malaria parasites, leading to inhibition of their growth.